Liquor among Teens: A Criminology Study (Law Research Review Quarterly, 2020)
This study aims to determine the effect of expectations on alcoholic drinks on the consumption of alcoholic drinks. Expectations on alcoholic beverages consist of positive expectations and negative expectations. Expectations on alcoholic drinks in this study refer to the notion that expectations are beliefs held by individuals in alcoholic drinks. Alcoholic drinks or, often called liquor (alcohol) is one type of drink that contains addictive substances (alcohol). More than 13 million people consider themselves alcoholics. Consumption of alcoholic drinks is divided into three types, namely (1) users, (2) abusers, and (3) dependency. The study was conducted on teenagers in Ambarawa who consume alcoholic beverages using quantitative methods with a survey model that is often also referred to as correlational research.